BIM TECHNOLOGY STRATEGIES IN DESIGNING SUSTAINABLE CITIES - SAEED , YOUSIF S. (Journal of Duhok University, 2023)
To prevent the serious environmental and economic damages resulting from the traditional state of the construction industry, global trend towards building sustainable cities is going on. Building Information Modeling (BIM) technology plays a prominent and effective role in achieving this trend in building called “smart” or “sustainable” cities in different phases of the construction starting from planning, design and, implementation phases and even also in managing after the occupation of the building. This paper highlights the importance of applying BIM technology in the field of sustainable cities by linking its tools to the construction industry by documenting these strategies and highlighting the effective role of the many applications of BIM technology in the planning, design, and implementation of sustainable green cities of high quality in conformity with the international standards adopted in the assessment of BIM. Also, it presents the state of the current obstacles that prevent the establishment of sustainable smart cities in Iraq, and take advantage of the applications of BIM technology to achieve this purpose, the main findings were concentrated on the most 10 obstacles facing application of BIM technology in Iraq and raising awareness and making decisions to start using BIM to save energy consumption, reduce the time and cost of projects, to keep pace with the modernity and great development in the field of construction technology, universities must be obliged to prepare qualified engineers to meet the requirements of the current technological reality in the construction industry, mandatory courses for preparing engineers working in the public and private sectors furthermore, companies and engineering departments in the government and private sector are encouraged to apply information modeling in the implementation of all construction projects in Iraq are the main contributions of this paper.